ANALISIS PERBANDINGAN MANAJEMEN KONFIGURASI MENGGUNAKAN ANSIBLE DAN SHELL SCRIPT PADA CLOUD SERVER DEPLOYMENT AWS: Array - Alfiandi, Tedi; Diansyah, T. M.; Liza, Risko (Universitas Harapan Medan, 2020)
Utilization of cloud computing technology in the development of a website has significant developments such as the use of disk storage, memory, and CPUs running in the cloud at a low cost when compared to physical servers. When creates a website, human interaction in carrying out the deployment process such as creating a database and installing the packages needed by the website, all of this is done manually so it takes a lot of time. An automation process is needed to solve this problem by using ansible and shell scripts in the website deployment process. This final project will compare ansible and shell scripts as configuration management for drupal deployments to the Amazon web service EC2 server by analyzing the deployment process time, CPU and memory usage on the server, throughput, and packet loss. Based on tests that shell scripts have performed outperformed ansible at deployment time with a difference of 3 minutes, troughput generated in ansible testing is better with an average of 60,164 Kb/s and 22,009 Kb/s for shell scripts, and ansible usage against the CPU is much better because it does not make the server overloaded.